Optogenetic Activation of A11 Region Increases Motor Activity - Koblinger, Kathrin; Jean-Xavier, Céline; Sharma, Sandeep; Füzesi, Tamás; Young, Leanne; Eaton, Shane E. A.; Kwok, Charlie Hong Ting; Bains, Jaideep Singh; Whelan, Patrick J. (Frontiers in Neural Circuits, 2018)
Limbic brain regions drive goal-directed behaviors. These behaviors often require dynamic motor responses, but the functional connectome of limbic structures in the diencephalon that control locomotion is not well known. The A11 region, within the posterior diencephalon has been postulated to contribute to motor function and control of pain. Here we show that the A11 region initiates movement. Photostimulation of channelrhodopsin 2 (ChR2) transfected neurons in A11 slice preparations showed that neurons could follow stimulation at frequencies of 20 Hz. Our data show that photostimulation of ChR2 transfected neurons in the A11 region enhances motor activity often leading to locomotion. Using vGluT2-reporter and vGAT-reporter mice we show that the A11 tyrosine hydroxylase positive (TH) dopaminergic neurons are vGluT2 and vGAT negative. We find that in addition to dopaminergic neurons within the A11 region, there is another neuronal subtype which express the monoenzymatic aromatic-L-amino acid decarboxylase (AADC), but not TH, a key enzyme involved in the synthesis of catecholamines including dopamine. This monoaminergic-based motor circuit may be involved in the control of motor behavior as part of a broader diencephalic motor region.